Prevalence of diagnosed HIV infection among persons with hepatitis C virus infection: England, 2008–2014. Issue 10 (26th July 2018) - Ireland, G; Delpech, V; Kirwan, P; Croxford, S; Lattimore, S; Sabin, C; Porter, K; Mandal, S; Simmons, R
Abstract : Objectives: In persons with hepatitis C virus (HCV) infection, HIV coinfection leads to faster progression to advanced liver disease. The aim of our study was to estimate diagnosed HIV prevalence among people with evidence of current HCV infection (polymerase chain reaction positive) and examine predictors of coinfection. Methods: Adults (≥ 15 years old) with a current HCV infection reported to the Public Health England (PHE) sentinel surveillance of blood‐borne viruses were linked to the PHE national HIV database using a deterministic methodology. Descriptive and multivariate analyses were conducted. Results: Between 2008 and 2014, 5.0% (999/20 088) of adults with a current HCV infection were diagnosed with HIV coinfection. The majority acquired HIV through sex between men (441; 64.9%), followed by injecting drug use (153; 22.5%) and heterosexual contact (84; 12.4%). Of persons who were coinfected, 65.5% had been diagnosed with HIV infection > 6 months before their HCV diagnosis, 41.4% of whom had a negative anti‐HCV test between their HIV and HCV diagnoses. In a multivariable model among persons with current HCV infection, an HIV diagnosis was more likely among men [adjusted odds ratio (aOR) 3.29; 95% confidence interval (CI) 2.60–4.16] and persons of black ethnicity (aOR 3.19; 95% CI 1.36–7.46), and less likely among older adults (aOR 0.85 per 10‐year increase; 95% CI 0.79–0.92) and persons of Asian ethnicity (aOR 0.59; 95% CI 0.41–0.86). Conclusions: Our results indicate that the majority of diagnosed HIV and current HCV coinfections are among men who have sex with men. Safer sex campaigns should include awareness of transmission of HCV among MSM living with HIV.